Analisis kemampuan disposisi matematis siswa SMP ditinjau dari self-regulated learning dalam studi kualitatif - Nurma Izzati; Nurul Aulia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study aims to describe the mathematical disposition profiles of students based on their level of Self-Regulated Learning (SRL). A qualitative descriptive method was employed, involving 32 eighth-grade students from SMP Negeri 8 Kota Cirebon. Findings indicate that students’ mathematical dispositions vary according to their SRL level. High SRL students exhibit consistently positive dispositions, particularly in perseverance, reflection, curiosity, and appreciation of mathematics. Medium SRL students show fairly good dispositions, although strategy management and self-evaluation are not yet optimal. Low SRL students display varied dispositions, with some affective aspects still developing despite limited self-regulation. These results highlight that students’ mathematical disposition profiles differ according to SRL levels, especially in internal aspects such as perseverance and reflection, while appreciation and application of mathematics can develop even with relatively low SRL. The study implies that teachers should strengthen students’ self-regulation while leveraging existing affective foundations. Limitations include a small sample size and focus on a single class, making the findings descriptive and not widely generalizable.